TINGKAT HASIL DAN KOMPONEN HASIL SISTEM INTENSIFIKASI PADI (SRI) TANPA PUPUK ORGANIK DI DAERAH CURAH HUJAN TINGGI - Masdar Masdar; Musliar Kasim; Bujang Rusman; Nurhajati Hakim; Helmi Helmi (Program Studi Ilmu Tanah Fakultas Pertanian UNIB, 2006)
Actually, the system of rice intensifications (SRI) have been encouraging the international researchers, included Indonesians, to intensively increase the yield. The system, such as regulations of planting points, numbers of seedling in each crop point, and planting time were applied here. The research was conducted in Limau Manis, aside the UNAND campus, from January to June 2005 used the varieties of Cisokan. The split plot design was applied in the research. The fertilizers were applied according to the recommended 200 kg urea, 200 kg SP-36, and 150 kg KCl. The research variables are harvest time, productive tillers, numbers of grain per panicle, grain weight, yield component, and yield. The data shows that relatively higher of monthly rainfalls and lower sunny days along the research periods have been the constrains in maximizing the crop production. Simply, the SRI application in the region was significantly useful due to the higher of both crop yield and yield component.